Bicolour electroluminescence of 2-(carbazol-9-yl)anthraquinone based on a solution process. Issue 46 (16th November 2017) - Huang, Bin; Li, Zijing; Yang, Hui; Hu, Die; Wu, Wenjing; Feng, Yan; Sun, Yueming; Lin, Baoping; Jiang, Wei
Abstract : Mechanochromic luminescence, thermally activated delayed fluorescence, aggregation-induced emission, and electroluminescence properties are combined in a single organic molecule, 2-(carbazol-9-yl)-anthraquinone (Cz-AQ). Abstract : Mechanochromic luminescence (ML), thermally activated delayed fluorescence (TADF), aggregation-induced emission (AIE), and electroluminescence (EL) properties are combined in a single organic molecule, 2-(carbazol-9-yl)-anthraquinone (Cz-AQ). Through controlling film formation in different solvents, the solution-processed nondoped devices utilizing Cz-AQ as the emitter exhibit bicolour emission with peaks at 600 and 680 nm, respectively.